The Impact of The Covid-19 Pandemic in Teaching and Learning Activity - Saputri, Eka Arifianti; Miftakh, Fauzi; Samsi, Yogi Setia (English Education: Jurnal Tadris Bahasa Inggris, 2021)
The emergence of Covid-19 some time ago had a huge impact on the world of education. Currently, the pandemic is still not over, but these difficulties cannot stop the nation's obligation to study and attend school. There have been many ways that have been done by the government, educators, and participants in getting around the best way to study during a pandemic. The government also decided that teaching and learning activities be carried out online so that students and teachers can avoid Covid-19. However, studying online is not as easy as it seems. Covid-19 has an effect that is felt by all educational groups, especially students. This study discusses the effects of Covid-19 on all students and learning personnel in teaching and learning activities. In addition, this article also provides an overview of how the proper teaching and learning process should be carried out so that the benefits of the process can be received equally from both parties.